COVID-19 Treatment: Drug Safety Prior to Conception and During Pregnancy and Breastfeeding - Cavalcante, Marcelo Borges; Cavalcante, Candice Torres de Melo Bezerra; Braga, Ana Catherine Sampaio; Andrade, Dennyse Araújo; Montenegro, Mariana Albuquerque; Santos, Paula Andrade Neiva; Motoyama, Paula Vitória Pereira; Rocha, Marcelo Gondim; Dib, Luciana Azôr; Araujo Júnior, Edward (Geburtshilfe und Frauenheilkunde, 2021)
In December 2019, a new viral respiratory infection known as coronavirus disease 2019 (COVID-19) was first diagnosed in the city of Wuhan, China. COVID-19 quickly spread across the world, leading the World Health Organization to declare it a pandemic on March 11, 2020. The disease is caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), a similar virus to those involved in other epidemics such as severe acute respiratory syndrome coronavirus (SARS-CoV) and Middle East respiratory syndrome coronavirus (MERS-CoV). Epidemiological studies have shown that COVID-19 frequently affects young adults of reproductive age and that the elderly and patients with chronic disease have high mortality rates. Little is known about the impact of COVID-19 on pregnancy and breastfeeding. Most COVID-19 cases present with mild flu-like symptoms and only require treatment with symptomatic relief medications, whereas other cases with COVID-19 require treatment in an intensive care unit. There is currently no specific effective treatment for COVID-19. A large number of drugs are being used to fight infection by SARS-CoV-2. Experience with this therapeutic arsenal has been gained over the years in the treatment of other viral, autoimmune, parasitic, and bacterial diseases. Importantly, the search for an effective treatment for COVID-19 cannot expose pregnant women infected with SARS-CoV-2 to the potential teratogenic risks of these drugs. Therefore, it is necessary to determine and understand the safety of anti-COVID-19 therapies prior to conception and during pregnancy and breastfeeding.
Keywords: COVID-19; SARS-CoV-2; antiviral; pregnancy; breastfeeding